Detailed Structure of the Subducted Nazca Slab into the Lower Mantle Derived From Continent‐Scale Teleseismic P Wave Tomography. Issue 5 (14th May 2020) - Portner, Daniel Evan; Rodríguez, Emily E.; Beck, Susan; Zandt, George; Scire, Alissa; Rocha, Marcelo P.; Bianchi, Marcelo B.; Ruiz, Mario; França, George Sand; Condori, Cristobal; Alvarado, Patricia
Abstract: Nazca subduction beneath South America is one of our best modern examples of long‐lived ocean‐continent subduction on the planet, serving as a foundation for our understanding of subduction processes. Within that framework, persistent heterogeneities at a range of scales in both the South America and Nazca plates is difficult to reconcile without detailed knowledge of the subducted Nazca slab structure. Here we use teleseismic travel time residuals from >1, 000 broadband and short‐period seismic stations across South America in a single tomographic inversion to produce the highest‐resolution contiguous P wave tomography model of the subducting slab and surrounding mantle beneath South America to date. Our model reveals a continuous trench‐parallel fast seismic velocity anomaly across the majority of South America that is consistent with the subducting Nazca slab. The imaged anomaly indicates a number of robust features of the subducted slab, including variable slab dip, extensive lower mantle penetration, slab stagnation in the lower mantle, and variable slab amplitude, that are incorporated into a new, comprehensive model of the geometry of the Nazca slab surface to ~1, 100 km depth. Lower mantle slab penetration along the entire margin suggests that lower mantle slab anchoring is insufficient to explain along strike upper plate variability while slab stagnation in the lower mantle indicates that the 1, 000 km discontinuity is dominant beneath South America. Key Points: High‐resolution teleseismic P wave tomography reveals the detailed structure of the subducted Nazca slab to lower mantle depths A new, comprehensive Nazca slab model is produced from the trench to 1, 100 km depth Lower mantle slab penetration occurs along the entire South American margin, inconsistent with variable upper plate shortening